STRES DAN KOMPONEN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Ailine Yoan Sanger; Ferdy Lainsamputty (Fakultas Ilmu Keperawatan Universitas Klabat, 2022)
Hypertensive patients are often found to suffer from psychological disorders. Stress in this population can disrupt the cardiovascular system which has the potential to worse the patient's condition. This study aimed to examine the relationship between stress and blood pressure components of hypertensive patients. Descriptive correlation design and cross-sectional approach were applied. A total of 196 hypertensive patients were recruited using a convenience sampling technique from a general hospital in Central Sulawesi, Indonesia. Descriptive statistics and Spearman correlation was used to examine the relationship between stress and blood pressure. The overall stress score was 24.29 (SD=6.36), with the dominant category was severe stress (48.4%). The participants' mean systolic blood pressure was 160.31 mmHg (SD=12.81) and diastolic was 85.97 mmHg (SD=7.55), the majority belonging to stage 2 hypertension. Systolic and diastolic blood pressure were not significantly correlated with stress (p>0.05). Doctors and nurses should not only pay attention to patient's blood pressure, but also focus on the psychological condition of patients. Future studies are expected to evaluate interventions that can reduce the psychological pressure of hypertensive patients.